PERBANDINGAN PENGATURAN DAN PENERAPAN MENGENAI TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN DI INDONESIA DAN DI INGGRIS: Comparison of Regulations and Implementation of Social and Environmental Responsibility in Indonesia and in the UK - Sudharmawan, M Naufal; Yunari, Sri Bakti (AMICUS CURIAE, 2024)
Corporate Social Responsibility (CSR) refers to the efforts of companies to assume social andenvironmental responsibility in their operations. CSR has been widely regulated and applied in variouscountries, including Indonesia and the UK. In Indonesia, Corporate Social and EnvironmentalResponsibility (CSER) is governed by a number of regulations, and PT Bank Central Asia Tbk (BCA) is acompany in Indonesia that has implemented various CSER initiatives in accordance with these regulations.In the UK, CSR is regulated under corporate law, and HSBC UK Bank plc (HSBC) is a company in theUK that has implemented various CSR initiatives in accordance with the regulation. The formulation ofthe problem in this study are: 1) What are the similarities and differences between CSER in Indonesia andCSR in the UK? 2) How is BCA's CSER in Indonesia and HSBC's CSR in the UK implements theregulation? This study used a normative legal research approach using secondary data. This research isdescriptive and conclusions are drawn through deductive reasoning. Based on the results of the research obtained, it can be concluded that Indonesia and the UK have several similarities and differences in legalarrangements and the application of CSER and CSR, respectively.